2019
DOI: 10.1016/j.ccell.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Early Detection of Cancer by Decoding the Epigenetic and Environmental Fingerprints of Cell-Free DNA

Abstract: Widespread adaptation of liquid biopsy for the early detection of cancer has yet to reach clinical utility. Circulating tumor DNA is commonly detected though the presence of genetic alterations, but only a minor fraction of tumor-derived cell-free DNA (cfDNA) fragments exhibit mutations. The cellular processes occurring in cancer development mark the chromatin. These epigenetic marks are reflected by modifications in the cfDNA methylation, fragment size, and structure. In this review, we describe how going bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
215
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(221 citation statements)
references
References 208 publications
(363 reference statements)
6
215
0
Order By: Relevance
“…This analytical approach allows by comparison of nuclear DNA from tissues for the determination of the relative contributions of various tissues in plasma DNA. For the design of our Figure, we were inspired by the figures in the publications of Van der Pol et Mouliere 8 and Murtaza et Caldas. 142 cfDNA fragmentation pattern analysis for better definition and detection of ctDNA Gel electrophoresis and electron microscopy were first used to analyse the length of cfDNA in the plasma or serum of cancer patients and healthy donors and revealed that plasma DNA is not randomly fragmented.…”
Section: Dna Fragmentation Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analytical approach allows by comparison of nuclear DNA from tissues for the determination of the relative contributions of various tissues in plasma DNA. For the design of our Figure, we were inspired by the figures in the publications of Van der Pol et Mouliere 8 and Murtaza et Caldas. 142 cfDNA fragmentation pattern analysis for better definition and detection of ctDNA Gel electrophoresis and electron microscopy were first used to analyse the length of cfDNA in the plasma or serum of cancer patients and healthy donors and revealed that plasma DNA is not randomly fragmented.…”
Section: Dna Fragmentation Patternsmentioning
confidence: 99%
“…66,[77][78][79] The 10-bp periodic oscillation observed might correspond to the wrapping and protecting of the DNA from enzymatic cleavage around the nucleosome or a protein complex. 8 Consequently, whether ctDNA is effectively shorter than nontumour cfDNA is a pivotal question. The detection of tumour-specific genetic alterations (including CNA and mutations) in human plasma and in the plasma of mice bearing human cancer xenografts revealed that mutant ctDNA is generally more fragmented than nonmutant cfDNA, with a maximum enrichment in fragments between 90 and 150 bp, 66,78 an observation that was harnessed to enhance mutation detection using either in vitro or in silico size selection.…”
Section: Dna Fragmentation Patternsmentioning
confidence: 99%
“…Changes (mutations, translocations, epigenetic marks) in the nucleic acid sequences that are only present within tumors can be detected in a cell-free state from small quantities of fluid (blood, CSF) among "a sea" of normal nucleic acid sequences. 4 In this issue, Bounajem et al and Azad et al describe how this "liquid biopsy" technology is being applied to the pediatric population with brain tumors. Some of the most important scientific advancements in tumor biology have been led by neurosurgeon scientists studying pediatric brain tumors.…”
mentioning
confidence: 99%
“…Second, cfDNA released into circulation is naturally fragmented by biological processes (Van Der Pol and Mouliere, 2019). Therefore, studying the fragmentation patterns of cfDNA is biologically relevant.…”
Section: Introductionmentioning
confidence: 99%